2010
DOI: 10.1071/cp09262
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose accumulation in sugarcane is influenced by temperature and genotype through the carbon source - sink balance

Abstract: While substantial effort has been expended on molecular techniques in an attempt to break through the apparent ceiling for sucrose content (SC) in sugarcane stalks, molecular processes and genetics limiting sucrose accumulation remain unclear. Our own studies indicate that limiting expansive growth with water stress will enhance sucrose accumulation in both low-and high-sucrose clones. Sucrose accumulation was largely explained (72%) by an equation with terms for photosynthesis, plant extension rate (PER), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…In sugarcane, upward flow to shoot growth centers was considerably more temperature sensitive than downward flow into mature culms (Hartt 1965), a response accounting for increased sucrose accumulation (Inman-Bamber et al 2010). Interestingly, estimates of Q 10 values for translocation out of leaf blades and down stems of 1.1 to 1.7 are suggestive of physiochemical-driven transport processes (Hartt 1965).…”
Section: Temperature Influences At Both Extremesmentioning
confidence: 99%
“…In sugarcane, upward flow to shoot growth centers was considerably more temperature sensitive than downward flow into mature culms (Hartt 1965), a response accounting for increased sucrose accumulation (Inman-Bamber et al 2010). Interestingly, estimates of Q 10 values for translocation out of leaf blades and down stems of 1.1 to 1.7 are suggestive of physiochemical-driven transport processes (Hartt 1965).…”
Section: Temperature Influences At Both Extremesmentioning
confidence: 99%
“…Disruption of the planting and harvesting schedule can have long-term effects over several seasons as growers attempt to return to schedules that have proven successful in the past. Temperature range is also known to be a good predictor of sucrose content (Kingston 2002) because low night temperatures discourage stalk (cane) and leaf growth, in favor of sucrose accumulation (Inman-Bamber et al 2010). We chose sugarcane yield as the target for our predictive model because of its importance in determining nitrogen requirements for the crop.…”
Section: Regression Random Forestmentioning
confidence: 99%
“…We chose sugarcane yield as the target for our predictive model because of its importance in determining nitrogen requirements for the crop. Low night temperatures would affect cane yield adversely (Inman-Bamber et al 2010).…”
Section: Regression Random Forestmentioning
confidence: 99%
“…For example, as a typical tropical and subtropical plant, sugarcane responds to chilling temperatures with dramatic alterations in photosynthesis, which is by far the most explored process in sugarcane for obvious reasons. For instance, under chilling temperature conditions, the photosynthetic rate is severely reduced (Inman-Bamber et al 2010). Furthermore, earlier studies carried out on leaves of a coldsensitive cultivar (Badila) revealed that important photosynthetic enzymes can be affected by chilling temperatures (10°C) such as decreased sucrose phosphate synthase (Du and Nose 2002), NADP-malate dehydrogenase and pyruvate orthophosphate dikinase activities (Du et al 1999), indicating a fundamental role of these enzymes when sugarcane is subjected to low temperatures.…”
Section: Temperature Stressmentioning
confidence: 97%